White Coat Hypertension in Aircrew: Diagnosis and Clinical Implications (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: When there is a difference of patient's blood pressure (BP) which is measured in a physician's office and patient’s home, it is said to have White Coat Hypertension (WCH). Prevalence of WCH is very much common among aircrew, because they need to face everyday preflight medical checkup.Objective: To find out the incidence of WCH among the aircrew of Bangladesh Air Force (BAF) as well as to ascertain the long-term clinical implications of WCH.Materials and Methods: This cross-sectional observational study was conducted among 150 aircrew, reported to Central Medical Board (CMB), Bangladesh Air Force (BAF) for periodical medical evaluation, during the period January 2014 to December 2018. Study subjects were selected purposively with age range 25-50 years; those who did not have any history of hypertension or received any anti-hypertensive medication but were detected elevated BP having clinical recording of BP ≥ 140/90 mm of Hg. Ambulatory blood pressure monitoring (ABPM) was performed on them for 24 hours in order to distinguish between those who were truly hypertensive and those who were suffering from WCH. To exclude secondary causes of hypertension as well as to assess for evidence of target organ damage (TOD), a thorough clinical and laboratory examination as well as regular follow-up were also performed.Results: White Coat Hypertension was observed in 26.7% of the aircrew. There was no evidence of target organ involvement, such as left ventricular dysfunction, left ventricular hypertrophy, hypertensive retinopathy or renal involvement.Conclusion: WCH is comparatively common among the aircrew. This highlights the importance of the requirement for regular follow up of all cases of WCH, over the normotensive subjects with a view to identify early organ involvement and therapeutic intervention are often initiated as and once needed.JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 14-17